Experimental Study on the Effect of Sand and Dust on the Performance of Photovoltaic Modules in Desert Areas - Xin Liu; Ningbo Wang; Mingzhi Zhao; Xiaoming Hu (Energies, 2024)
Photovoltaic power generation is one of the most effective measures to reduce greenhouse gas emissions, and the surface of photovoltaic modules in desert areas is mainly affected by sand erosion and cover, which affect power output. Therefore, a wind–sand erosion system was established to simulate the desert wind–sand environment, analyze the influence of dust erosion on the output power of the component, and observe the surface erosion morphology of the component. Then, dust particles of different sizes were selected to cover the surface of the photovoltaic module, and the temperature change and output characteristics of the backplane of the module were studied. The results show that the erosion rate increases with the increase in the erosion angle. When the erosion rate is 25 m/s and 30 m/s, the output power decreases by 9.82%~16.00% and 15.42%~24.46% at different erosion angles, respectively. As the particle size (0.05 mm~0.30 mm) deposited on the surface of the photovoltaic module gradually increases, the open-circuit voltage of the module changes little, and its maximum difference is 0.25 V. Short-circuit current and output power vary greatly; the maximum difference in short-circuit current is about 13.00%, and the maximum difference in output power is about 17.00%. Through our research, this study provides a certain reference for maximizing power generation efficiency and the clean planning of desert photovoltaic power stations.